The investigation of fraud related to the involvement of citizens for housing construction - Kusmartsev, Volodymyr; Vorko, Yevhen (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
Article is an analysis of the investigation of fraud related to the involvement of citizens for housing construction. The article describes the essence and structure of the real estate. Clarified ways to counter such fraud and the proposed system improvements in financial control of enterprises of the construction complex.